Character Taxonomy in Dina Rubina’s Trilogies of the 2000s— 2010s - E. V. Merkel; E. S. Tulusheva (Научный диалог, 2020)
The article examines the trilogy by Dina Rubina “People of the Air” (2008—2010) and “Russian Canary” (2014). The relevance of the study is due, firstly, to the low degree of study of the trilogy “Russian Canary” (the onomastic space of the work is analyzed and the features of the book are determined in the context of a family novel of the 20th century); secondly, the need to differentiate the author’s artistic methodology, which is different in the studied macro-texts. The novelty of the research is seen in the fact that the authors, comparing the two trilogies by Dina Rubina, come to the conclusion that the author uses various semiotic strategies for constructing texts, thus revealing the homology of storylines, methods of constructing character series and general principles of world modeling of trilogies. The results of a comparative analysis are presented, which allow us to see the patterns of the artistic search of a modern author and his stylistic innovations. It is proved that with the parallelism of character series of two epic cycles, the author in the first case resorts to the artistic method of magical realism (“People of the Air”), and in the second case uses realistic principles of writing (“Russian Canary”).